A novel type of splayed ferromagnetic order observed in Yb2Ti2O7. (25th August 2016) - Yaouanc, A; Dalmas de Réotier, P; Keller, L; Roessli, B; Forget, A
Abstract: The pyrochlore insulator Yb2 Ti2 O7 has attracted the attention of experimentalists and theoreticians alike for about 15 years. Conflicting neutron diffraction data on the possible existence of magnetic Bragg reflections at low temperature have been published. Here we report the observation of magnetic Bragg reflections by neutron powder diffraction at 60 mK. The magnetic diffraction pattern is analyzed using representation theory. We find Yb2 Ti2 O7 to be a splayed ferromagnet as reported for Yb2 Sn2 O7, a sibling compound with also dominating ferromagnetic interactions as inferred from the positive Curie–Weiss temperature. However, the configuration of the magnetic moment components perpendicular to the easy axis is of the all-in–all-out type in Yb2 Ti2 O7 while it is two-in–two-out in the Yb2 Sn2 O7 . An overall experimental picture of the magnetic properties emerges.